The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/pharmaceutics11070359
|View full text |Cite
|
Sign up to set email alerts
|

Effective Therapeutic Delivery and Bioavailability Enhancement of Pioglitazone Using Drug in Adhesive Transdermal Patch

Abstract: The administration of pioglitazone as an oral therapy is restricted due to various challenges. The aim of the current investigation was to evaluate the suitability of pioglitazone in adhesive transdermal patch as an alternative delivery system, in order to improve therapeutic delivery. Drug in adhesive pioglitazone (2% w/w) transdermal patch were optimized for drug release, suitable adhesive, and skin permeation enhancer. The selected patch was examined for drug-loading capacity and the patch with greater piog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Regarding the effects observed during the use of pioglitazone, it has been mainly reported that it increases insulin sensitivity, interference with lipid homeostasis, and regulation of the inflammatory response. Thus, many efforts have been made in the development of formulations for the topical use of pioglitazone ( Silva-Abreu et al., 2017 ; Nair et al., 2019 ; Rojewska et al., 2020 ), opening new expectations for the treatment of skin diseases such as CL. Indeed, patients with psoriasis treated with topical pioglitazone had a decreased severity in disease score ( Mittal et al., 2009 ; Singh and Anil, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects observed during the use of pioglitazone, it has been mainly reported that it increases insulin sensitivity, interference with lipid homeostasis, and regulation of the inflammatory response. Thus, many efforts have been made in the development of formulations for the topical use of pioglitazone ( Silva-Abreu et al., 2017 ; Nair et al., 2019 ; Rojewska et al., 2020 ), opening new expectations for the treatment of skin diseases such as CL. Indeed, patients with psoriasis treated with topical pioglitazone had a decreased severity in disease score ( Mittal et al., 2009 ; Singh and Anil, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The micrograph of the film was captured on a Nova NanoSEM 450 (FEI Ltd., Hillsboro, OR, USA) equipped with a large field detector. The film was mounted using silver electrical tape and sputter coated (SCD005 Baltek Sputter Coater, Baltec, AG, Balzers, Liechtenstein, Germany) with gold in the presence of argon gas under reduced pressure [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…This patch gained the largest share of the nitroglycerin industry. Nitro-Dur II ® was the brand name for the patch, which was later sold and listed in a US patent [77].…”
Section: From the Ointment To The Transdermal Patches: Nitroglycerin ...mentioning
confidence: 99%